An orbital shear platform for real‐time, in vitro endothelium characterization. Issue 6 (28th January 2016) - Velasco, Vanessa; Gruenthal, Mark; Zusstone, Esther; Thomas, Jonathan M. D.; Berson, R. Eric; Keynton, Robert S.; Williams, Stuart J.
ABSTRACT: Electrical impedance techniques have been used to characterize endothelium morphology, permeability, and motility in vitro. However, these impedance platforms have been limited to either static endothelium studies and/or induced laminar fluid flow at a constant, single shear stress value. In this work, we present a microfabricated impedance sensor for real‐time, in vitro characterization of human umbilical vein endothelial cells (HUVECs) undergoing oscillatory hydrodynamic shear. Oscillatory shear was applied with an orbital shaker and the electrical impedance was measured by a microfabricated impedance chip with discrete electrodes positioned at radial locations of 0, 2.5, 5.0, 7.5, 10.0, and 12.5 mm from the center of the chip. Depending on their radial position within the circular orbital platform, HUVECs were exposed to shear values ranging between 0.6 and 6.71 dyne/cm 2 (according to numerical simulations) for 22 h. Impedance spectra were fit to an equivalent circuit model and the trans‐endothelial resistance and monolayer's capacitance were extracted. Results demonstrated that, compared to measurements acquired before the onset of shear, cells at the center of the platform that experienced low steady shear stress (∼2.2 dyne/cm 2 ) had an average change in trans‐endothelial resistance of 6.99 ± 4.06% and 1.78 ± 2.40% change in cell capacitance after 22 hours of shear exposure; cells near the periphery of the well ( r = 12.5 mm) experienced transient shears (2.5–6.7 dyne/cm 2 ) and exhibited a greater change in trans‐endothelial resistance (24.2 ± 10.8%) and cell capacitance (4.57 ± 5.39%). This study, demonstrates that the orbital shear platform provides a simple system that can capture and quantify the real‐time cellular morphology as a result of induced shear stress. The orbital shear platform presented in this work, compared to traditional laminar platforms, subjects cells to more physiologically relevant oscillatory shear as well as exposes the sample to several shear values simultaneously. Biotechnol. Bioeng. 2016;113: 1336–1344. © 2015 Wiley Periodicals, Inc. Abstract : A range of hydrodynamic shear is applied to an endothelial cell monolayer. The monolayer's integrity is monitored in real time via AC impedance.